Bridging the gap : notes on an engendered approach to social work with Caribbean elders - Baker, Peta-Anne (WAND St. MichaelBB, 1995)
Makes proposals for social work interventions with Caribbean elders which both focus on the needs of this particular group, and also adopt the modality of engendering, especially with respect to addressing the strategic needs of elders (male and female), as distinct from their survival or immediate needs. Addresses the implications of this approach for the training of social workers and other professional working with Caribbean elders within the region.